2022
DOI: 10.1001/jamanetworkopen.2022.44849
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adherence to Endocrine Therapy Among Patients With Breast Cancer and Potential Drug-Drug Interactions

Abstract: ImportanceSuboptimal adherence to endocrine therapy (ET) among patients with hormone-receptor–positive breast cancer significantly affects survival outcomes and is associated with higher hospitalization rates and health care costs. Weak adherence to long-term treatments has multiple determinants, including disease characteristics, treatment adverse effects, and patients’ attributes, such as age and comorbidities.ObjectiveTo examine whether potential drug-drug interactions (PDDI) with tamoxifen or aromatase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Additionally, the low representation of young and old patients (patients < 30 years n = 7 [0.8%] and those >70 years n = 57 [6.1%]) limits the generalizability of our findings to these demographic groups and points out the need for tailored strategies to address them. Participants who discontinued treatment early for tolerance/personal reasons could be less likely inclined to answer the survey, explaining the low rate of nonadherence and early discontinuation of ET in our cohort ( n = 88; 9.4%) in comparison to the published literature 9 , 35 . The survey did not assess subjective (patient-reported) or biologic (hormonal levels) measures of adherence to the prescribed therapy, nor did it evaluate compliance with the prolonged use of the application.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, the low representation of young and old patients (patients < 30 years n = 7 [0.8%] and those >70 years n = 57 [6.1%]) limits the generalizability of our findings to these demographic groups and points out the need for tailored strategies to address them. Participants who discontinued treatment early for tolerance/personal reasons could be less likely inclined to answer the survey, explaining the low rate of nonadherence and early discontinuation of ET in our cohort ( n = 88; 9.4%) in comparison to the published literature 9 , 35 . The survey did not assess subjective (patient-reported) or biologic (hormonal levels) measures of adherence to the prescribed therapy, nor did it evaluate compliance with the prolonged use of the application.…”
Section: Discussionmentioning
confidence: 71%
“…Compliance to ET is known to be suboptimal, since rates reportedly range between 50% and 89% of the patients. 10 , 11 , 12 Studies have shown that the survival of patients with HR-positive BC is strongly linked to adherence to ET, particularly in the adjuvant setting. In the French CANTO cohort, serum assessment of tamoxifen identified 16.0% of patients (n = 188) below the set adherence threshold.…”
Section: Introductionmentioning
confidence: 99%